(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
This paper analyzes the manuscript tradition of Dante’s so-called “Garisenda sonnet” (LI; 42) and proposes some alternative solutions compared to the critical edition by Domenico De Robertis (2002).